Heterogeneous human capital: Perspectives on income inequality and leadership in technology - Elise S. Brezis; Amir Rubin (Bar-Ilan University, Department of Economics, 2024)
This paper highlights a new driver of inequality, that may become increasingly prominent over the years: the inequality between skilled workers graduating from elite universities and those from standard institutions. This paper emphasizes that heterogeneity in higher education is a key factor in understanding both inequality and technological leadership. We introduce a new framework for analyzing economic growth, inequality, and leadership in technology, diverging from traditional innovation models by incorporating the concept of heterogeneity in higher education. The paper shows that a disparity between elite and standard universities not only contributes to inequality but also fosters technological leadership. The disparity between universities is referred to as the "duality gap", and it measures the distinctions between elite and non-elite universities in quality, budgets as well as tightness of students' recruitment. In the empirical part of the paper, we check the relationships developed in the theoretical model. To do so, we develop an index of the duality gap both in quality and tightness of recruitment for 17 OECD countries. The data indeed show a positive correlation between the indices of duality gap, leadership in technology, and inequality among OECD countries.
Keywords: I26; J24; O14; O4; 330; ability; heterogeneity; productivity; duality gap; higher education; quality of education; wage premium; international leadership; tightness of students' recruitment